Global justice and territory - Nine, Cara. (Oxford : Oxford University Press, 2012)
Historical injustice and global inequality are basic problems embedded in territorial rights. In 'Global Justice and Territory' Cara Nine advances a general theory of territorial rights adapting a theoretical framework from natural law theory to ground all territorial claims.
Description based on online resource; title from PDF title page (viewed on July 5, 2012).
Includes bibliographical references and index.
Keywords: Territory, National; Jurisdiction, Territorial; Self-determination, National